ANALISIS PENGELOLAAN ALOKASI DANA DESA BERBASIS VALUE FOR MONEY STUDI PADA DESA PINANG LUAR - Susanti, Lisa (Jurusan Akuntansi FEB UNTAN, 2024)
The management of village fund allocation must ensure that every allocated rupee has a maximum impact on the development and welfare of the village community. The concept of